(untitled) (Journal of Academic Research, 2018)
The interval estimation of the Poisson parameter is commonly presented problem in textbook. The Wald interval is the most frequently used confidence interval for estimating Poisson parameter, and it is based on the asymptotic properties of the sample mean. The Wald interval has a chaotic behaviour in terms of coverage probability, particularly when is small. The well known Score interval is recommend by many authors as an alternative to the Wald interval. This paper proposes a new confidence interval for estimating that has a better performance in terms of coverage probability than the Wald interval as well as smaller confidence width than the Score interval.